Adaptation and Assessment of Psychometric Properties of the Brief Sensation-seeking Scale in an Indonesian General Sample - Bagaskara, Sunu (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2021)
This study aimed to examine the psychometric properties of the Brief Sensation-seeking Scale (BSSS, Hoyle et al., 2002) in an Indonesian sample. A set of questionnaires consisting of an adaptation of the BSSS, Ten Item Personality Inventory (TIPI)-Indonesia, and a risky driving behavior scale were administered to 360 participants with an average age of 25.23 years. The reliability test using the internal consistency method showed high reliability (α=0.79). CFA analysis shows that the factor structure of the 4-factor BSSS-Indonesia model is more fit to the data than the 1-factor model. Construct validity was also found from the results of the correlation analysis of the BSSS-I score with the personality traits of openness to experience (convergent), agreeableness, and conscientiousness (discriminant). Regarding demographics, it was found that there were differences in the average scores between both sexes and age groups. The BSSS-I score was also found to be a significant predictor of risky driving behavior (concurrent validity). Taken together, the findings of this study show satisfactory evidence of psychometric properties, in line with previous adaptation of BSSS in several other cultures. This indicates that the BSSS-I is a sound instrument to measure trait sensation-seeking in the Indonesian population.